2006
DOI: 10.1111/j.1096-3642.2006.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

The origin of mammalian endothermy: a paradigm for the evolution of complex biological structure

Abstract: Several mutually incompatible theories exist about how and why endothermy evolved in mammals and birds. Some take the primary function to have been thermoregulation, selected for one adaptive purpose or another. Others take the high aerobic metabolic rate to have been primary. None of these theories is incontrovertibly supported by evidence, either from the fossil record of the synapsid amniotes or from observations and experiments on modern organisms. Furthermore, all are underpinned by the tacit assumption t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
138
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(153 citation statements)
references
References 48 publications
3
138
0
2
Order By: Relevance
“…Some have suggested that ridges on the internal surfaces of the nasal cavity of therocephalians, a lineage of nonmammalian therapsids that is the sister taxon to cynodonts, served for attachment of turbinal elements (Hillenius, 1994). However, the interpretation of these ridges is debated in the literature (e.g., Kemp, 2006) and there are no preserved ossified turbinals in these specimens. Furthermore, ossified turbinals were not observed in key nonmammalian cynodont taxa (e.g., Hadrocodium wui; Macrini, 2006;Rowe et al, 2011) that are closely related to crown Mammalia.…”
Section: Ancestral Reconstruction Of Number Of Turbinalsmentioning
confidence: 88%
“…Some have suggested that ridges on the internal surfaces of the nasal cavity of therocephalians, a lineage of nonmammalian therapsids that is the sister taxon to cynodonts, served for attachment of turbinal elements (Hillenius, 1994). However, the interpretation of these ridges is debated in the literature (e.g., Kemp, 2006) and there are no preserved ossified turbinals in these specimens. Furthermore, ossified turbinals were not observed in key nonmammalian cynodont taxa (e.g., Hadrocodium wui; Macrini, 2006;Rowe et al, 2011) that are closely related to crown Mammalia.…”
Section: Ancestral Reconstruction Of Number Of Turbinalsmentioning
confidence: 88%
“…In chickens however, the increases in oxidative capacity (state 3 respiration rate) are accompanied by increased uncoupling of oxidative phosphorylation and increased cellular ATP demand, both of which reduce the ATP available for activity. It is unlikely, therefore, that the advantages of increased activity or any other single initial selection pressure led to modern endothermic phenotypes (Kemp, 2006). Complex organismal functions such as endothermy evolve by the gradual integration of genetic changes that affect suborganismal traits, without the need for evolutionary transitions of individual traits to contribute directly to the more complex function (Lenski et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to mammals (Kemp, 2006), the origin and mechanisms that led to endothermy in the Archosauria is controversial and one of the most hotly debated topics in vertebrate evolution (Gillooly et al, 2006;Seebacher, 2003;Seymour et al, 2004). At present there is no agreement even about whether ancestral archosaurs were endotherms or ectotherms (Ruben, 1995;Seymour et al, 2004), although there is little doubt that ectothermy is ancestral to endothermy (Hillenius and Ruben, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of endothermy, the ability to maintain high and stable body temperatures through internal heat production, is a major physiological change that occurred at an unknown stage during the evolutionary transition to mammals and birds from their ancestors among the nonmammalian therapsids and nonavian dinosaurs, respectively (1). Approaches to understanding the physiology of extinct animals and the evolution of endothermy have largely focused on biophysical modeling, anatomical observations, growth rate analysis from bone histology, and behavioral studies such as estimating predator/prey ratios (1)(2)(3)(4)(5)(6)(7). The validity of each of these approaches is uncertain (for contrasting viewpoints on approaches to dinosaur thermoregulation see refs.…”
mentioning
confidence: 99%